(untitled) (Sains Humanika, 2012)
This article discusses various issues of work ethics among public servants in Malaysia. Among the discussion in this article is a macro approach on the development efforts in developing the work ethics in this country since the 1980s to this day. It will also examine the micro view of the work ethics practice among civil servants in the principles of neutrality and public interests, which are the two core principles of public servants. Therefore this article will critically examines the efforts of public service reforms, better known as the New Trends in Public Management or New Public Management (NPM) implemented since the 1980s.